Enhance Design Of Iot Smart Control Home Lighting System Based On Arduino - Muhammad Salim; Solly Aryza; Siti Anisah (Sean Institute, 2021)
In the future, technological development factors greatly affect the human ability to carry out activities. To do simple things is sometimes difficult for some people. This difficulty is encountered in the elderly and children when reaching the switch to turn on electronic equipment such as lights. In this study, the latest research on controlling lights using voice commands is carried out. The convenience provided is controlling the lights with voice commands using an android smartphone. This tool is made to replace the function of the switch so that it can ON/OFF the lights without having to reach the switch that is far from the user. The working principle is explained below. The user will give voice commands through the Boarduino application on the Android cellphone, where Android has been connected to Arduino Uno via Bluetooth HC-05 as the transmission medium. The sound is detected by Google Voice and then stored and recorded by the microphone on the cellphone. The recorded voice is sent to Google's servers via the internet, then Google reads and processes the human voice. By sampling the sound that was previously an analog signal into binary (digital) bits. Furthermore, these bits are processed in the Google database and translated into text form. Every voice command will be processed by Arduino Uno, if the voice command is by the program then the relay is active so that the lights can be controlled. This tool is expected to be able to meet the needs and right on target in the community. And become a tool to meet needs, especially for the elderly and children.